2021
DOI: 10.1155/2021/5560714
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Knowledge among College of Basic Education Students in Kuwait: A Cross-Sectional Study

Abstract: Lack of nutrition knowledge may contribute to poor dietary practices. Schools are an ideal environment to address this issue and to start the process of nutrition education. Therefore, teachers should be equipped with adequate nutrition knowledge. This study was designed to evaluate the level of general nutrition knowledge and demographic variations in knowledge in a sample of students attending the College of Basic Education in Kuwait. A cross-sectional study was conducted using a modified and validated revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…This is unexpected because about 67% had education spanning from Junior High School to tertiary level. This result is however similar to the findings of Husain et al 36 who observed poor NK among prospective teachers studying in the College of Basic Education in Kuwait. Provision of nutrition education for the market traders may help improve their level of knowledge as published by Elmas and Arslan 37 …”
Section: Discussionsupporting
confidence: 91%
“…This is unexpected because about 67% had education spanning from Junior High School to tertiary level. This result is however similar to the findings of Husain et al 36 who observed poor NK among prospective teachers studying in the College of Basic Education in Kuwait. Provision of nutrition education for the market traders may help improve their level of knowledge as published by Elmas and Arslan 37 …”
Section: Discussionsupporting
confidence: 91%
“…It was demonstrated that nutrition knowledge was satisfactory for 34.7% of women and 40.2% of men, while it was good for 34.7% of women and 25.1% of men, respectively [ 37 ]. Other studies determined the level of their knowledge as good [ 38 , 39 ], below average [ 40 ], but also, as in our study, the nutrition knowledge was assessed as low [ 41 , 42 ]. The inconsistent results obtained in different studies may result from the field of the study, but also from the specificity of the measurement tools [ 37 , 42 ].…”
Section: Discussionmentioning
confidence: 52%
“…Other studies determined the level of their knowledge as good [ 38 , 39 ], below average [ 40 ], but also, as in our study, the nutrition knowledge was assessed as low [ 41 , 42 ]. The inconsistent results obtained in different studies may result from the field of the study, but also from the specificity of the measurement tools [ 37 , 42 ]. A higher similarity of the results was obtained from the studies that used the same tool, for example, the General Nutrition Knowledge Questionnaire (GNKQ) [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It was reported that women had better knowledge about nutrition than men [ 32 ]. In our study, women also had a better grasp of dairy knowledge than men, which might be associated with the fact that women pay more attention to health.…”
Section: Discussionmentioning
confidence: 99%